The reality of benefiting from virtual laboratories in teaching science in the secondary stage in Jeddah - Bujaily, Fatima Abdullah (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the reality of benefiting from virtual laboratories in teaching science in the secondary stage in Jeddah, and identify the requirements and obstacles of their use, and ways to develop them. The researcher used the analytical descriptive approach, and the questionnaire was used as a tool for the study. The study was applied to a sample of (275) teachers of physics and chemistry and laboratory secretaries in the secondary stage. The study revealed a number of results, the most important of them are: Virtual laboratories serve the field of education efficiently and easily and that the technology of virtual laboratories is a good alternative in the case of absence of chemicals and equipment and educational supplies. Based on the results, the study suggested a number of recommendations, the most important of them are, that the ministry of education should continue in expanding the integration of science teaching between virtual laboratories and traditional laboratories.
Keywords: virtual laboratories; science; secondary school; Jeddah governorate